Disruption Events Sebagai Peristiwa Yang Tak Terduga Dalam Pelaksanaan Kewajiban Kontraktual - Sugiastuti, Natasya Yunita; Hertanto, Ari Wahyudi; Setiawati, Anda; Wijaya, Agung; Putra, Ghayana Aditya (UI Scholars Hub, 2024)
An agreement creates an obligation, which is a legal relationship between the parties. If one party fails to fulfill its duties to the other party as promised, it is considered a breach of contract by one party against the other. One of the external factors that disrupt contract execution is a disruption event. In contrast to the concepts of force majeure and hardship, which have been acknowledged in Indonesian law, the argument of disruption events has not been recognized, even in the context of legal literature. However, in certain contracts with extended durations, the concept of disruption event has been incorporated into the creation of an accidental provision. This accidental provision is intended to address unforeseen events that may impair the contract's implementation. Given the importance of regulating disruption events in the agreement clause to anticipate the legal consequences that arise if an event occurs that disrupts the implementation of the contract, this research raises two issues: 1) What is the nature or essence of a disruption event? and 2) How is the formulation of an anticipatory disruption event clause in the contract? As a result of the research, it can be concluded that a disruption event is an unpredictable event that significantly impacts the industry and business. 2) A disruption event clause must at least contain information about the following: the definition of a disruption event, the scope or limits of a disruption event, the obligation to notify the affected party of a disruption event, the legal effects of a disruption event on contractual obligations and on the relationship between contractors, and the possibility of negotiation.